PERLINDUNG HUKUM TERHADAP KORBAN KEKERASAN (Analisis Kasus Penganiayaan dan Penistaan Seksual Pada Bulan Mei 2024 di Palu) - I Putu Wira Aditya; Lenny Nadriana (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2025)
The case of the assault and nudity of a 15-year-old teenager in Palu by two women in May 2024 highlights the complexity of violent crimes, particularly when involving female perpetrators and child victims, and their legal implications. Protection of victims, particularly children and those whose dignity has been degraded, is a priority. This study aims to analyze the laws and regulations related to the protection of victims of assault and nudity in Palu, and to identify the roles and responsibilities of law enforcement officials in providing legal protection. The research method used is a normative one, with a statute approach, using secondary data from a literature review, and qualitative analysis through interpretation of legal materials. The results show that the old and new Criminal Codes (KUHP), the Child Protection Law, and the Witness and Victim Protection Law provide a comprehensive legal framework. The New Criminal Code regulates sexual assault and defamation in more detail (Article 414), while the Child Protection Law provides harsher sanctions for violence against children (Article 80 paragraph 1). The Witness and Victim Protection Law guarantees victims' rights. Law enforcement officials (Police, Prosecutors, Courts, and the Witness and Victim Protection Agency) have a clear, hierarchical role, from rapid response, investigation, prosecution, to sentencing and restitution, which is vital in ensuring protection and justice for victims.